Analysis of practices to promote reproducibility and transparency in anaesthesiology research. (November 2020) - Okonya, Ochije; Rorah, Drayton; Tritz, Daniel; Umberham, Blake; Wiley, Matt; Vassar, Matt
Abstract: Introduction: Reliable, high-quality research is essential to the field of anaesthesiology. Reproducibility and transparency have been investigated in the biomedical domain and in the social sciences, with both lacking to provide necessary information to reproduce the study findings. In this study, we investigated 14 indicators of reproducibility in anaesthesiology research. Methods: We used the National Library of Medicine catalogue to search for all anaesthesiology journals that are MEDLINE indexed and provide English texts. PubMed was searched with the list of journals to identify all publications from January 1, 2014 to December 31, 2018. We randomly sampled 450 publications that fit the inclusion criteria for our analysis. Data extraction was then conducted in a blinded, duplicate fashion using a pilot-tested Google form. Results: The PubMed search of these journals identified 171 441 publications, with 28 310 being within the time frame. From the 450 publications sampled, 444 full-text publications were accessible. The majority of publications analysed did not have a statement regarding availability of data (164/188), analysis scripts (187/188), or study materials (160/188). Conclusions: Anaesthesiology research needs to improve indicators of reproducibility and transparency. By making research publicly available and improving accessibility to detailed study components, primary research can be reproduced in subsequent studies and help contribute to the development of new practice guidelines.